Advanced computational models for disturbed and turbulent flow in stenosed human carotid artery bifurcation - Tan,FPP; Soloperto,G; Wood,NB; Thom,S; Hughes,A; Xu,XY (Ifmbe Proceedings, 2008)
In this study, newly developed two-equation transitional and turbulence models are employed for the prediction of blood flow patterns in diseased carotid artery where the growth, progression and structure of plaque at rupture are closely linked to low and oscillating wall shear stresses. Moreover, laminar-turbulent transition in the post-stenotic zone can alter the separation zone length, wall shear stress and pressure distribution over the plaque, with potential implications for stresses within the plaque. A separate validation study was carried out with well established experimental measurements and numerical studies. Laminar flow, Menter's hybrid k-ε/k-ω Shear Stress Transport model and its transitional version were implemented in pulsatile simulations from which analyses of velocity profiles, wall shear stress and turbulence intensity were conducted. It was found that the transitional version of SST gave better overall agreement with experimental data for pulsatile flow in an axisymmetric stenosed tube and this is further highlighted in the patient-specific geometry simulation results. A magnetic-resonance (MR) image based model of the carotid bifurcation with 70% stenosis was reconstructed and simulated using patient-specific boundary conditions. The laminar flow assumption was found to be inadequate when the differences occurred in the wall shear stress analysis of the patient-derived model. © 2008 Springer-Verlag.